“Let It Be.” Heidegger’s Conception of Technology Between Enframing and Releasement (KULT_online, 2020)
In Heidegger on Technology, Aaron James Wendland, Christopher Merwin, and Christos Hadjioannou analyze Martin Heidegger’s multifaceted engagement with modern technology by taking into account texts on the subject only recently translated and published in English. The volume brings together 17 contributions by renowned experts who develop and interpret Heidegger’s thoughts on our technological age. Furthermore, this essay collection probes fruitful appropriations of Heidegger’s philosophy of technology in the study of culture.